Conformity Of Curriculum Management Of The Pancasila Student Profile Strengthening Project (P5) In Vocational Schools With Industrial Needs - Hakim, Lukman (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2024)
Vocational High Schools, abbreviated as SMK, are schools that produce graduates who are ready to work with the competencies, skills, and character needed by the industrial world. The existence of graduates who have the competencies, skills, and character is supported by the existence of a curriculum that can deliver graduates who are expected by the industrial world. In this case, the independence curriculum with the P 5 program (Pancasila Student Profile Strengthening Project). Producing graduates who have meaningful learning experiences for students, where they are directly involved in project activities that are relevant to real life and issues around them in this case the industrial world. With P5, students are expected to be able to develop various competencies, such as: Faith, devotion to God Almighty, and noble character, independence, mutual cooperation, global diversity, critical thinking, and creativity. The industrial world needs skilled and integrated workers. So that the suitability of the independence curriculum with the P 5 program as an answer to the needs of the industrial world.